VERTIGO SENTRAL: TINJAUAN TERKINI MENGENAI PATOFISIOLOGI DAN STRATEGI DIAGNOSIS - Sutarni, Sri; Setyaningrum, Cempaka Thursina Srie; Ar Rochmah, Mawaddah; Bayuangga, Halwan Fuad (PERDOSNI, 2025)
Recent advances have fundamentally reshaped the clinical and pathophysiological landscape of central vertigo, moving beyond a simplistic brainstem model to a sophisticated understanding of a distributed central vestibular network. This network, encompassing the brainstem, cerebellum, thalamus, and cortex, provides a robust framework for explaining how disruptions from stroke, demyelination, or functional disorders produce diverse symptoms. In parallel, diagnostic paradigms have evolved dramatically. The advent of quantitative ocular motor testing, epitomized by the HINTS protocol and enhanced by video-head impulse testing (vHIT), now allows for highly sensitive bedside identification of central causes in acute settings. Furthermore, advanced neuroimaging techniques, including optimized diffusion-weighted and vessel wall MRI, have revolutionized our ability to detect subtle posterior fossa infarcts and vascular pathology. These mechanistic and technological insights have also refined our perspective on specific syndromes, solidifying vestibular migraine and persistent postural-perceptual dizziness (PPPD) as central disorders of sensory integration. Ultimately, the integration of this modern network-based pathophysiology with targeted diagnostic tools is establishing a new standard of care, significantly improving diagnostic accuracy, enabling timely intervention, and guiding future therapeutic development for patients with central vertigo. Keywords: Vestibular network, HINTS examination, neuroimaging, acute vestibular syndrome, central vertigo